Cost and availability optimization of wind energy with distributed energy resources of a microgrid. Issue 6 (December 2019) - Ramabhotla, Sundari; Bayne, Stephen B
A microgrid, an emerging technology in the electric power systems, has various benefits due to the implementation of distributed energy sources along with the loads. A microgrid utilizing the wind energy, solar energy, combined heat and power, natural gas generator, diesel generator, and battery storage is considered in an islanded mode of operation. The economic dispatch optimization is implemented using a reduced gradient algorithm to optimize the Operation and Maintenance cost in the islanded mode of the microgrid. The cost of each energy source is evaluated for every hour of the day using MATLAB code. Then, the availability of each energy source in the microgrid is evaluated. The results obtained are validated by comparing the Operation and Maintenance cost and the availability of each energy source in the microgrid. The optimal solution is achieved by considering the change in wind forecast and battery energy storage profiles.